Boy : Tales of Childhood - Dahl, Roald (UK Puffin Books, 1984)
Presents humorous anecdotes from the author's childhood which includes summer vacations in Norway and an English boarding school.
Include Illustration
Keywords: Manners and customs -- Great Britain -- Boarding schools